The Drifter - Plumley, Lisa (London Harlequin, 2002)
Advice From Miss Julia's Behavior Book A proper lady should never give her heart to a driftin' man! Mistress of decorum, Julia Bennett wrote the book on etiquette. Three volumes, in fact! So why did the arrival of Graham Corley, rakish adventurer, give her decidedly improper ideas.' Bounty hunter, rogue, drifter-and now fiancE for hire to the most tantalizing woman in the Territories! Damn, Graham Corley led an interesting life-and being partner to Julia Bennett's outrageous finagling to secure her inheritance made it downright fascinating! Maybe even enough to give this travelin'man dreams about staying put.!
Keywords: a